Leukoencephalopathy with calcifications and cysts: A case report. Issue 29 (July 2017) - Ma, Yubao; Zhang, Xingwen; Cheng, Chen; Xu, Quangang; Di, Hai; Zhao, Jiao; Huang, Dehui; Yu, Shengyuan
Abstract: Rationale: Leukoencephalopathy with calcifications and cysts (LCC) is an uncommon entity characterized by edematous leukoencephalopathy, cerebral calcifications, and parenchymal cysts. Due to its rarity, the clinical, radiological, and histopathological features have yet to be well elucidated. Patient concerns: The first case is a 35-year-old female who was asymptomatic. A giant intracranial cyst was incidentally detected radiologically, and it was slowly growing in the recent 10 years. The second case is a 20-year-old female who presented with a 1-month history of headache. Brain computed tomography showed multiple asymmetric calcifications in the bilateral basal ganglia and white matter. Magnetic resonance imaging revealed a cyst in the right parietal lobe. Diagnoses: They were diagnosed with LCC. Interventions and Outcomes: The first patient underwent surgical resection of the intracranial cyst, and the second patient received a stereotactic biopsy. The patients performed well postoperatively. Lessons: LCC can be found at any age. A young age seems to be associated with severer symptoms. The clinical manifestations can be variable and aggressive. The potential pathogenic basis still needs further research.